PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE BOWLING KAMPUS UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS XI IPA SMA HANDAYANI PEKANBARU - Rahma Lisa Indrayani; Betty Holiwarni; Miharthy Miharthy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: Research on the application of the active learning strategy type bowling campus has been done to improve students learning achievement in the topics of atomic structure and periodic system of unsure in class XI IPA of SMA Handayani Pekanbaru. This research is experiment based on pretest-posttest design. The sample consisted of two classes, which are XI IPA 1 as experiment class and XI IPA 3 as control clas that randomly selected after testing normality and homogeneity. The active learning strategy type bowling campus applied in experiment class that while in the control class the active learning strategy type bowling campus was applied. Analyzed of data used t-test. Results of the analysis it was found that tscore>ttable (2,8947>1,67), it means the active learning strategy type bowling campus can improve students learning achievement on atomic structure and periodic system of unsure in class XI IPA of SMA Handayani Pekanbaru. The improvement of learning achivement in the experiment class was supported by influence coefficient value of 9,93%.Key Words: active learning strategy type bowling campus, learning achievement